Evaluasi Kandungan Hasil Pengolahan Limbah Cair pada Unit Effluent Treatment Pabrik III B PT. Petrokimia Gresik - Latfiara Zahra; Praditya Sigit Ardisty Sitogasa; Erik Priyanto (Yayasan Literasi Sains Indonesia, 2023)
Fertilizer is a supporter of the country's food security, the government through State-Owned Enterprises (BUMN), one of which is PT Petrokimia Gresik, which is the most complete and largest fertilizer producer in Indonesia which produces several wastes, one of which is industrial wastewater. The existence of liquid waste is not expected in the environment because it has no economic value, therefore the need for waste treatment is very important. PT Petrokimia Gresik uses physical processing and chemical processing. PT Petrokimia Gresik has a wastewater treatment plant with a series of processes consisting of 2 effluent treatment units, equalizer, line injection, Urea Plant hydrolizer stripper, and sludge treatment. The parameters analyzed were Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Ammonia (NH3), Total Kjehdal Nitrogen (TKN), Fluoride, Degree of Acidity (pH), Oil and Fat. After conducting the research, the results of the analysis showed that the effluent pollutant load data was at the quality standards regulated in regulations. However, it was found that the results of TKN (Total Kjeldahl Nitrogen) or the amount of bound nitrogen in an organic substance varied.